1981
DOI: 10.1007/bf00251276
|View full text |Cite
|
Sign up to set email alerts
|

HLA-D and -DR antigens in genetic analysis of insulin dependent diabetes mellitus

Abstract: Three groups of patients with insulin-dependent diabetes mellitus, ascertained by different procedures, were investigated for HLA-A, B, C and D antigens (n = 164), and a subset (n = 93) for HLA-DR. Both HLA-D/DR3 and D/DR4 were strongly positively associated and D/DR2 was negatively associated with insulin-dependent diabetes. HLA-DR+ was found to be a better marker for insulin-dependent diabetes than Dw4. The HLA-B associations (B8, B15 and B18) were clearly secondary to the increases of HLA-D/DR3 and D/DR 4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
107
2
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(120 citation statements)
references
References 28 publications
10
107
2
1
Order By: Relevance
“…This is in line with previous studies reporting that HLA-DR3 and HLA-DR4 were strongly associated with Type I diabetes among Caucasians [18][19][20], except that HLA-DRw9 found in Japanese patients was substituted for HLA-DR3 in Caucasian patients. The previous studies failed to show the association of HLADRw9 with Type 1 diabetes among Japanese [13,14].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in line with previous studies reporting that HLA-DR3 and HLA-DR4 were strongly associated with Type I diabetes among Caucasians [18][19][20], except that HLA-DRw9 found in Japanese patients was substituted for HLA-DR3 in Caucasian patients. The previous studies failed to show the association of HLADRw9 with Type 1 diabetes among Japanese [13,14].…”
Section: Discussionsupporting
confidence: 93%
“…Myasthenia gravis, which is an autoimmune disease directed to acetylcholine receptors of the neuromuscular junction, is similar in that its HLA-association varies among different ethnic groups; HLA-DR2 and DR3 in Caucasians [24], HLA-DR4 in Chinese [25], and HLADRw8 and DRw9 in Japanese [26]. These ethnic differences in HLA-association with Type I diabetes or myasthenia gravis might be derived from the difference in the distribution of HLA-DR antigens among the general population of the races; the prevalence of HLA-DR3 antigen is negligibly low not only in Type 1 diabetic patients but also in normal subjects, among Japanese as shown in the present study and previous studies [13,14,16], while it is considerably high even in the general population of Caucasians [18][19][20] and Chinese [23,25]. In this study, we found that HLA phenotype of DRw9 and HLA haplotype of Bw61-DRw9 were increased in Type 1 diabetic patients who had organspecific autoantibodies other than ICA; whereas HLA phenotype of DR4 and HLA haplotype of Bw54-DR4 were increased in those who did not have any autoantibodies.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Since the risk of developing persistent proteinuria is significantly higher for diabetics who are 0-10 years old at diagnosis than in patients with a later onset of diabetes [13], it has been suggested that there may be different types of insulin dependent diabetes, one with an early onset which is associated with the antigens HLA-Dw4 and DR4 and another with onset around puberty and associated mainly with HLA-Dw3 and DR3 [14]. It is possible that the first type is associated with an early and total lack of endogenous insulin secretion and a predisposition to develop nephropathy, while the second type is associated with an insidious onset of B cell insufficiency and a lesser predisposition to develop nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…There may be a link between these immunopathological phenomena and the observation that Type 1 diabetes is associated with certain HLA-DR determinants, in particular HLA-DR3 and HLA-DR4 [4,5]. More than 90% of caucasoid children with Type 1 diabetes carry one or both of these specificities [5].…”
mentioning
confidence: 99%